Designing a Data-Driven E-Learning Module for Teaching English to Young Learners: Integrating Needs Analysis and the ISAV Learning Model - Endah Ratnaningsih; Erna Andriyanti; Dyah Setyowati Ciptaningrum; Arum Nisma Wulanjani; Nurrofiqi Ankisqiantari (ASEAN Journal of Educational Research and Technology, 2027)
This study designed a data-driven e-learning module for Teaching English to Young Learners by integrating needs analysis with the Interactive, Somatic, Auditory, and Visual learning model. Using a design-based research approach, the study focused on the analysis and design phases. Data were collected from elementary school English teachers and pre-service English teachers through a structured questionnaire addressing necessities, lacks, and wants. The findings identified vocabulary, reading, and oral communication as key learning necessities, alongside difficulties in sentence structure and broader instructional constraints. Respondents also preferred interactive and multimodal learning activities. These findings informed an ISAV-based e-learning module prototype integrating interactive, somatic, auditory, and visual features to support learner-centered, multimodal, and contextually responsive English instruction for young learners in digital environments.